The Role of Village-Owned Enterprises (BUMDes) in People's Economic Empowerment in Tanggulangin Village Pasuruan Regency - Safitri, Dewi Fayruz; Daryono; suchaina (Jurnal Dinamika Sosial Ekonomi, 2025)
This study aims to analyze the role of BARETA Village-Owned Enterprises (BUMDes) in the economic empowerment of the community of Tanggulangin Village, Pasuruan Regency, with a focus on the influence of management assistance, Corporate Social Responsibility (CSR) support, and the use of grant funds in strengthening the local economy. The method used is a qualitative approach through interviews, observations, and documentation of BUMDes administrators, village officials, and the community. The results of the study show that BUMDes BARETA plays an important role in increasing community income, creating new jobs, and encouraging the strengthening of entrepreneurship based on local potential. Synergy between BUMDes, village governments, and the private sector through Nestlé's CSR program also strengthens managerial capacity and access to capital. However, the challenges faced include limited human resources, business innovation, and financial independence. Professional and participatory management of BUMDes is the key to the sustainability of the village economy. Therefore, it is necessary to increase financial literacy, business management training, and strengthen multi-stakeholder collaboration to accelerate the sustainable economic transformation of the community at the village level.